A dialog and a communication: the contemporary problems of formation of the communicative competence of the artists (based on the examples of the art students) - Ibragimov, Aman (Pedagogy and Psychology, 2021)
This article reveals the issues of development and formation of communicative competence among students of an art specialty. The study revealed that an insufficient level of speech culture is typical for students of future artists and teachers. This problem is most acutely expressed by the excessive enthusiasm of students for art and visual activity with insufficient attention to the development of communication skills and a departure from professional self-determination. The purpose of the article is to identify the results of the formation of the subject communicative competence of students of art specialties in the learning process. The following methods were used in the study: theoretical (review, analysis and synthesis of literature); empirical (pedagogical observation, oral and written surveys, tests, pedagogical experiment). The study was conducted at the Institute of Arts, Culture and Sports of KazNPU named after Abai among students (17-19) years old. The data indicate that the formation of communicative competence needs pedagogical support in preparing students for professional activities. The problem of low speech culture of students, inability to communicate, express their thoughts, and sometimes vice versa, upholding the position of a human consumer negatively affects the professional development of the future artist and teacher. The analysis shows that against the background of a general drop in the level of literacy and speech culture of young people, the communicative competence of artists is an urgent problem for many specialties, including for students of pedagogical universities.